Articular Cartilage Dynamics - Smith, David W.; Gardiner, Bruce S.; Zhang, Lihai; Grodzinsky, Alan J. (Springer Nature Singapore : Imprint: Springer, 2019)
This book explains the anatomy and physiology of cartilage tissue in an integrated way. The emphasis is on how cartilage tissue functions and maintains homeostasis in a challenging mechanical environment. Supported by hundreds of references, the book posts new hypotheses explaining how cartilage adapts and achieves homeostasis in vivo, and tests them against available data. This exploratory approach creates a sense of discovery that the reader can join, or perhaps test themselves through their own research. The main benefit will be obtained by research students and professors looking to understand the deeper concepts that will further their own research, or clinicians (including health professionals and surgeons) who want to gain a deeper physiological understanding of cartilage tissue, which can then serve as a basis for more rational clinical decision-making they need to make on a daily basis. To help bridge the gap between basic science and clinically relevant joint disease, applications and interpretations of key physiological concepts are discussed in the context of osteoarthritis at the end of most chapters.